PENERAPAN METODE PEMBELAJARAN MATEMATIKA REALISTIK DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA PADA SISWA KELAS VI SD NEGERI 163091 TEBING TINGGI - Marlina Naipospos (Universitas Negeri Medan, 2019)
This aims to improve math learning achievement through mathematic realistic method. This classroom action researchconducted by 2 cycles of the four phases: planning, implementation, observation, reflection. The subjects were students from class VI, SD N 163091 Tebing Tinggi which amounted to 33 students. This study used a qualitative descriptive analysis technique. The results showed that the used of the mathematic realistic method of math subjects can improve math learning result characterized by increased learning completeness, which occured in first cycle (78,78%), cycle II (90,90%) and complete learning the clasical equal to 93,93 %. Keywords : Math, Realistic